Talking about sex after cancer: A discourse analytic study of health care professional accounts of sexual communication with patients - Ussher, Jane M.; Perz, Janette; Gilbert, Emilee; Wong, W.K. Tim; Mason, Catherine; Hobbs, Kim; Kirsten, Laura (Psychology & health, 2013)
There is consistent evidence that health care professionals (hcps) are not addressing the sexual information and support needs of people with cancer. Thirty-eight Australian hcps across a range of professions working in cancer care were interviewed, to examine constructions of sexuality post-cancer, the subject positions adopted in relation to sexual communication, and the ways in which discourses and subject positions shape information provision and communication about sexuality. Participants constructed sexual changes post-cancer in physical, psychological and relational terms, and positioned such changes as having the potential to significantly impact on patient and partner well-being. This was associated with widespread adoption of a discourse of psychosocial support, which legitimated discussion of sexual changes within a clinical consultation, to alleviate distress, dispel myths and facilitate renegotiation of sexual practices. However, this did not necessarily translate into patient-centred practice outcomes, with the majority of participants positioning personal, patient-centred and situational factors as barriers to the discussion of sex within many clinical consultations. This included: absence of knowledge, confidence and comfort; positioning sex as irrelevant or inappropriate for some people; and limitations of the clinical context. In contrast, those who did routinely discuss sexuality adopted a subject position of agency, responsibility and confidence.